Corrosion-resistant anchor rod and production process thereof

Through the corrosion-resistant anchor process of hot-dip galvanizing and passivation treatment, the content of Dy, W and Mo is optimized, and the chemical substances in the passivation liquid are used to form a protective film, which solves the problem of poor mechanical properties of corrosion-resistant anchors, which is significantly It improves the corrosion resistance and mechanical properties of the anchor rod and enhances the safety of underground operations.

CN119144901AActive Publication Date: 2024-12-17HANDAN YONGNIAN DISTRICT XINKUI IND & MINING ACCESSORIES MANUFACTURING CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411362741.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-17
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing corrosion-resistant anchors have poor mechanical properties and are difficult to adapt to the current complex working environment, which increases safety hazards for underground operations.

Method used

The corrosion-resistant anchor process using hot-dip galvanizing and passivation treatment is adopted to optimize the weight percentage of Dy, W and Mo in the anchor body, and to utilize carboxymethyl dextran, iminodisuccinic acid and Modified nano-silicon nitride forms a dense protective film to improve the corrosion resistance and mechanical properties of the anchor.

Benefits of technology

It significantly improves the mechanical properties and corrosion resistance of the anchor, reduces the corrosion rate and failure possibility of the anchor in complex environments, and enhances the safety of underground operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of anchor rods, and provides a corrosion-resistant anchor rod and a production process thereof, the corrosion-resistant anchor rod is obtained by carrying out hot galvanizing and passivating treatment on an anchor rod body, and the anchor rod body is prepared from the following components in percentage by weight: 0.55%-0.75% of Mn, 0.035%-0.055% of Mo, 0.15%-0.25% of C, 0.015%-0.035% of Dy, 0.05%-0.25% of V, 0.025%-0.045% of Gd, 0.01%-0.025% of W and the balance of iron and inevitable impurities. By means of the technical scheme, the problem that the mechanical property of a corrosion-resistant anchor rod is poor in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anchor rods, and in particular to a corrosion-resistant anchor rod and a production process thereof. Background Art

[0002] Anchor rods are tensile components that penetrate deep into the strata, mainly used to reinforce rock and soil to prevent deformation or collapse. Especially in the field of coal mining technology, anchor rods can be used as support measures to ensure the stability of tunnels and ensure the safety of underground operations in coal mines. At present, many mining areas in my country have entered the deep mining stage. With the continuous deepening of mining depth, the reliability of the anchoring system is becoming more and more important. However, with the deepening of mining depth, the underground working environment becomes more and more complex, and is always affected by environmental factors such as mine water, surrounding rock clay, and mine atmosphere. The corrosion of anchor rods used to fix the tunnels becomes more and more serious, increasing the possibility of anchor rod failure and increasing the safety hazards of underground operations. Therefore, corrosion-resistant anchor rods came into being. However, at this stage, corrosion-resistant anchor rods have the problem of poor mechanical properties and are difficult to adapt to the current working environment. How to improve the mechanical properties of corrosion-resistant anchor rods is a technical problem that needs to be solved urgently. Summary of the invention

[0003] The invention provides a corrosion-resistant anchor rod and a production process thereof, which solves the problem of poor mechanical properties of the corrosion-resistant anchor rod in the related art.

[0004] The technical solution of the present invention is as follows: The present invention provides a corrosion-resistant anchor rod, which is obtained by hot-dip galvanizing and passivation treatment of an anchor rod body, wherein the anchor rod body is composed of the following components in percentage by weight: Mn 0.55%~0.75%, Mo 0.035%~0.055%, C 0.15%~0.25%, Dy 0.015%~0.035%, V0.05%~0.25%, Gd 0.025%~0.045%, W 0.01%~0.025%, and the rest are iron and unavoidable impurities.

[0005] As a further technical solution, the weight ratio of the sum of the weights of Dy and W to Mo is 0.8~1:1.

[0006] When the weight ratio of Dy and W to Mo is 0.8~1:1, the mechanical properties of the anchor can be further improved.

[0007] As a further technical solution, the weight ratio of Dy to W is 1:1.

[0008] The present invention also provides a production process for a corrosion-resistant anchor rod, comprising the following steps: S1, mixing the components in the weight percentage, smelting, and casting to obtain a casting billet; S2, heat-treating the ingot, rolling, drawing, and threading the ingot to obtain an anchor body; S3, the anchor body is pickled, washed with water, hot-dip galvanized, passivated and cooled to obtain a corrosion-resistant anchor.

[0009] As a further technical solution, in step S3, during the hot-dip galvanizing treatment, the zinc liquid is composed of the following components in weight percentage: Pb 0.1%~0.2%, Sn 0.05%~0.1%, Bi 0.05%~0.1%, Sb 0.03%~0.1%, and the rest is zinc and unavoidable impurities.

[0010] As a further technical solution, in step S3, during the hot-dip galvanizing treatment, the thickness of the galvanized layer is 15-20 μm.

[0011] As a further technical solution, in step S3, during the passivation, a passivation solution is used, and the passivation solution includes the following components in parts by weight: 25-35 parts of chromium nitrate, 3-18 parts of carboxymethyl dextran, 10-15 parts of sodium molybdate, 4-11 parts of iminodisuccinic acid, 6-10 parts of potassium sodium tartrate, 8-22 parts of nano silicon nitride, and 100 parts of water.

[0012] The passivation liquid includes carboxymethyl dextran and iminodisuccinic acid. Through the reasonable use of carboxymethyl dextran and iminodisuccinic acid, the effect of the passivation liquid and the metal ions on the surface of the anchor body can be enhanced, so that a denser and more stable protective film is formed on the surface of the anchor body, thereby further improving the corrosion resistance of the anchor.

[0013] As a further technical solution, the weight ratio of the carboxymethyl glucan to the iminodisuccinic acid is 1-1.5:1.

[0014] When the weight ratio of carboxymethyl glucan to iminodisuccinic acid is 1-1.5:1, the corrosion resistance of the anchor rod can be further improved by reasonably regulating the contents of carboxymethyl glucan and iminodisuccinic acid.

[0015] As a further technical solution, the nano silicon nitride is modified nano silicon nitride, and the raw materials of the modified nano silicon nitride include nano silicon nitride and ternary hydroxychloroacetic acid resin.

[0016] The surface of nano silicon nitride is modified by ternary hydroxychloroacetic acid resin, so that nano silicon nitride is not easy to agglomerate in the passivation solution, and the interaction with carboxymethyl dextran and iminodisuccinic acid can be strengthened, thereby enhancing the passivation effect of the passivation solution on the surface of the anchor body, thereby further improving the corrosion resistance of the anchor.

[0017] As a further technical solution, the preparation method of the modified nano silicon nitride comprises the following steps: dissolving the ternary hydroxychloroacetic acid resin in ethyl acetate to obtain a ternary hydroxychloroacetic acid resin solution, adding the nano silicon nitride to the ternary hydroxychloroacetic acid resin solution, dispersing evenly, and concentrating to obtain modified nano silicon nitride.

[0018] As a further technical solution, the mass fraction of the tertiary hydroxychloroacetic acid resin solution is 5% to 10%.

[0019] As a further technical solution, the weight ratio of the nano silicon nitride to the ternary hydroxychloroacetic acid resin is 9-19:1.

[0020] When the weight ratio of nano silicon nitride to ternary hydroxychloroacetic acid resin is 9-19:1, the corrosion resistance of the anchor rod can be further improved.

[0021] As a further technical solution, in step S2, during the heat treatment, the temperature is 1000-1200°C and the insulation time is 30-60 minutes.

[0022] As a further technical solution, in step S2, the rolling includes rough rolling and finish rolling. During the rough rolling, the starting rolling temperature is 900-1000°C; during the finish rolling, the starting rolling temperature is 850-950°C.

[0023] As a further technical solution, during the passivation, the temperature of the passivation solution is 100-120° C., and the passivation time is 2-5 min.

[0024] The working principle and beneficial effects of the present invention are: In the present invention, the anchor body is subjected to hot-dip galvanizing and passivation treatment, so that the anchor has good corrosion resistance. By optimizing the content of each component in the anchor body, the advantages of each component can be complemented, thereby improving the mechanical properties of the anchor, wherein the weight percentage of Dy, W and Mo is reasonably regulated, and the mechanical properties of the anchor can be significantly improved by the reasonable combination of the three. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the following embodiments and comparative examples, the manganese content in the manganese iron alloy is 68wt%; the Mo content in the molybdenum iron alloy is 60wt%; the Dy content in the dysprosium iron alloy is 80wt%; the V content in the vanadium iron alloy is 50wt%; the Gd content in the gadolinium iron alloy is 73wt%; the W content in the tungsten iron alloy is 80wt%; the iron content in the scrap steel is 97.6wt%; the model of the ternary hydroxychloroacetic acid resin is TP-500A; the particle size of the nano silicon nitride is 100nm; and the thickness of the corrosion-resistant anchor rod galvanized layer is 18μm.

[0027] Example 1 A corrosion-resistant anchor rod, which is obtained by hot-dip galvanizing and passivation treatment of the anchor rod body, and the anchor rod body is composed of the following components in weight percentage: Mn 0.55%, Mo 0.035%, C 0.15%, Dy 0.015%, V 0.05%, Gd 0.025%, W 0.01%, the rest is iron and inevitable impurities; During hot-dip galvanizing, the zinc solution is composed of the following components in weight percentage: Pb 0.15%, Sn 0.08%, Bi0.08%, Sb 0.05%, and the rest is zinc and unavoidable impurities; The passivation solution includes the following components in parts by weight: 25 parts of chromium nitrate, 10 parts of sodium molybdate, 6 parts of potassium sodium tartrate, 8 parts of nano silicon nitride, 100 parts of water; The production process of corrosion-resistant anchor rods includes the following steps: S1, mixing ferromanganese alloy, ferromolybdenum alloy, ferrodysprosium alloy, ferrovanadium alloy, ferrogadolinium alloy, ferrotungsten alloy and scrap steel according to the above weight percentages, smelting, casting, and obtaining a casting ingot; S2, heat treating the ingot at 1000°C, keeping the temperature for 60 minutes, rough rolling at 900°C, finishing rolling at 850°C, drawing, threading, and obtaining the anchor body; S3. After pickling, water washing and hot-dip galvanizing, the anchor body is passivated in a passivation solution at a temperature of 120°C for 2 minutes and cooled to obtain a corrosion-resistant anchor.

[0028] Example 2 A corrosion-resistant anchor rod, which is obtained by hot-dip galvanizing and passivation treatment of the anchor rod body, and the anchor rod body is composed of the following components in weight percentage: Mn 0.6%, Mo 0.054%, C 0.2%, Dy 0.018%, V 0.15%, Gd 0.035%, W 0.018%, the rest is iron and inevitable impurities; During hot-dip galvanizing, the zinc solution is composed of the following components in weight percentage: Pb 0.15%, Sn 0.08%, Bi0.08%, Sb 0.05%, and the rest is zinc and unavoidable impurities; The passivation solution includes the following components in parts by weight: 25 parts of chromium nitrate, 10 parts of sodium molybdate, 6 parts of potassium sodium tartrate, 8 parts of nano silicon nitride, 100 parts of water; The production process of corrosion-resistant anchor rods includes the following steps: S1, mixing ferromanganese alloy, ferromolybdenum alloy, ferrodysprosium alloy, ferrovanadium alloy, ferrogadolinium alloy, ferrotungsten alloy and scrap steel according to the above weight percentages, smelting, casting, and obtaining a casting ingot; S2, heat treating the ingot at 1100°C, keeping the temperature for 45 minutes, rough rolling at 950°C, finishing rolling at 900°C, drawing, threading, and obtaining the anchor body; S3. After pickling, water washing and hot-dip galvanizing, the anchor body is passivated in a passivation solution at a temperature of 110°C for 4 minutes and cooled to obtain a corrosion-resistant anchor.

[0029] Example 3 A corrosion-resistant anchor rod, which is obtained by hot-dip galvanizing and passivation treatment of the anchor rod body, and the anchor rod body is composed of the following components in weight percentage: Mn 0.75%, Mo 0.055%, C 0.25%, Dy 0.035%, V 0.25%, Gd 0.045%, W 0.025%, the rest is iron and inevitable impurities; During hot-dip galvanizing, the zinc solution is composed of the following components in weight percentage: Pb 0.15%, Sn 0.08%, Bi0.08%, Sb 0.05%, and the rest is zinc and unavoidable impurities; The passivation solution includes the following components in parts by weight: 25 parts of chromium nitrate, 10 parts of sodium molybdate, 6 parts of potassium sodium tartrate, 8 parts of nano silicon nitride, 100 parts of water; The production process of corrosion-resistant anchor rods includes the following steps: S1, mixing ferromanganese alloy, ferromolybdenum alloy, ferrodysprosium alloy, ferrovanadium alloy, ferrogadolinium alloy, ferrotungsten alloy and scrap steel according to the above weight percentages, smelting, casting, and obtaining a casting ingot; S2, heat treating the ingot at 1200° C., keeping the temperature for 30 min, rough rolling at 1000° C., finishing rolling at 950° C., drawing, threading, and obtaining the anchor body; S3. After pickling, water washing and hot-dip galvanizing, the anchor rod body is passivated in a passivation solution at a temperature of 100°C for 5 minutes and cooled to obtain a corrosion-resistant anchor rod.

[0030] Example 4 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the anchor body contains Dy in an amount of 0.024% by weight, W in an amount of 0.024% by weight, and Mo in an amount of 0.042% by weight.

[0031] Example 5 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the anchor body contains Dy in an amount of 0.02% by weight, W in an amount of 0.02% by weight, and Mo in an amount of 0.05% by weight.

[0032] Example 6 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the anchor body contains Dy in an amount of 0.0225% by weight, W in an amount of 0.0225% by weight, and Mo in an amount of 0.045% by weight.

[0033] Example 7 The difference between this embodiment and embodiment 6 is that, in this embodiment, the passivation solution includes the following components in parts by weight: 25 parts of chromium nitrate, 7 parts of carboxymethyl dextran, 10 parts of sodium molybdate, 6 parts of potassium sodium tartrate, 8 parts of nano silicon nitride, and 100 parts of water.

[0034] Example 8 The difference between this embodiment and embodiment 6 is that, in this embodiment, the passivation solution includes the following components in parts by weight: 25 parts of chromium nitrate, 10 parts of sodium molybdate, 7 parts of iminodisuccinic acid, 6 parts of potassium sodium tartrate, 8 parts of nano silicon nitride, and 100 parts of water.

[0035] Example 9 The difference between this embodiment and embodiment 6 is that, in this embodiment, the passivation solution includes the following components in parts by weight: 25 parts of chromium nitrate, 3 parts of carboxymethyl dextran, 10 parts of sodium molybdate, 4 parts of iminodisuccinic acid, 6 parts of potassium sodium tartrate, 8 parts of nano silicon nitride, and 100 parts of water.

[0036] Example 10 The difference between this embodiment and embodiment 6 is that, in this embodiment, the passivation solution includes the following components in parts by weight: 30 parts of chromium nitrate, 9.5 parts of carboxymethyl dextran, 13 parts of sodium molybdate, 10.5 parts of iminodisuccinic acid, 8 parts of potassium sodium tartrate, 20 parts of nano silicon nitride, and 100 parts of water.

[0037] Embodiment 11 The difference between this embodiment and embodiment 6 is that, in this embodiment, the passivation solution includes the following components in parts by weight: 35 parts of chromium nitrate, 18 parts of carboxymethyl dextran, 15 parts of sodium molybdate, 11 parts of iminodisuccinic acid, 10 parts of potassium sodium tartrate, 22 parts of nano silicon nitride, and 100 parts of water.

[0038] Example 12 The only difference between this embodiment and embodiment 10 is that in this embodiment, 13 parts of carboxymethyl dextran and 7 parts of iminodisuccinic acid are added to the passivation solution.

[0039] Embodiment 13 The only difference between this embodiment and embodiment 10 is that in this embodiment, 10 parts of carboxymethyl dextran and 10 parts of iminodisuccinic acid are added to the passivation solution.

[0040] Embodiment 14 The only difference between this embodiment and embodiment 10 is that in this embodiment, 12 parts of carboxymethyl dextran and 8 parts of iminodisuccinic acid are added to the passivation solution.

[0041] Embodiment 15 The only difference between this embodiment and Embodiment 14 is that in this embodiment, the nano silicon nitride is modified nano silicon nitride, and the preparation method of the modified nano silicon nitride comprises the following steps: dissolving 3 parts of ternary hydroxychloroacetic acid resin in ethyl acetate to obtain a ternary hydroxychloroacetic acid resin solution with a mass fraction of 6%, adding 17 parts of nano silicon nitride to the ternary hydroxychloroacetic acid resin solution with a mass fraction of 6%, dispersing evenly, and concentrating to obtain modified nano silicon nitride.

[0042] Example 16 The only difference between this embodiment and embodiment 15 is that, in this embodiment, 19.5 parts of nano silicon nitride and 0.5 parts of ternary hydroxychloroacetic acid resin are added.

[0043] Embodiment 17 The only difference between this embodiment and embodiment 15 is that, in this embodiment, 19 parts of nano silicon nitride and 1 part of ternary hydroxychloroacetic acid resin are added.

[0044] Embodiment 18 The only difference between this embodiment and embodiment 15 is that, in this embodiment, 18 parts of nano silicon nitride and 2 parts of ternary hydroxychloroacetic acid resin are added.

[0045] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, the anchor body does not contain Mo, and contains Dy in an amount of 0.036% by weight and W in an amount of 0.024% by weight.

[0046] Comparative Example 2 The only difference between this comparative example and Example 1 is that in this comparative example, the anchor body does not contain Dy, and contains W in an amount of 0.025% by weight and Mo in an amount of 0.035% by weight.

[0047] Comparative Example 3 The only difference between this comparative example and Example 1 is that in this comparative example, the anchor body does not contain W, but contains Dy in an amount of 0.025% by weight and Mo in an amount of 0.035% by weight.

[0048] Comparative Example 4 The only difference between this comparative example and Example 1 is that in this comparative example, the anchor body does not contain Dy and W, and contains Mo in an amount of 0.06% by weight.

[0049] Comparative Example 5 The only difference between this comparative example and Example 1 is that in this comparative example, the anchor body does not contain Dy, W and Mo.

[0050] Experimental Example 1 Mechanical Properties Test The anchor bodies prepared in Examples 1 to 6 and Comparative Examples 1 to 5 were tested for tensile strength and yield strength according to the test method in GB / T 228.1-2021 "Tensile test of metallic materials - Part 1: Room temperature test method", wherein the test speed was 0.006s -1 , the test result is the average value of 5 samples.

[0051] The test results are shown in Table 1 below: Table 1 Test results

[0052] In Table 1, compared with Comparative Examples 1 to 5, the tensile strength and yield strength of the anchor body prepared in Example 1 are significantly improved, indicating that when the anchor body contains Dy, W and Mo, the weight percentages of Dy, W and Mo can be reasonably adjusted to significantly improve the mechanical properties of the anchor. In addition, compared with Examples 2 and 4, the tensile strength and yield strength of the anchor bodies prepared in Examples 5 to 6 are improved, indicating that when the weight ratio of Dy and W to Mo is 0.8 to 1:1, the mechanical properties of the anchor can be further improved.

[0053] Experimental Example 2 Corrosion resistance test ① The corrosion-resistant anchors prepared in Examples 6 to 18 were tested for corrosion resistance according to the copper-accelerated acetic acid salt spray test method in GB / T 10125-2021 "Artificial atmosphere corrosion test salt spray test", and the surface of the samples was observed for rust, wherein the test temperature was 50°C and the test period was 720h; ② The corrosion-resistant anchors prepared in Examples 6 to 18 were subjected to a sodium chloride salt solution immersion test according to the test method in GB / T 19746-2018 “Corrosion salt solution immersion test for metals and alloys”. The test period was 4 weeks. The mass loss of the samples before and after the immersion test was recorded, and the corrosion rate was calculated. The concentration of the sodium chloride solution was 35 g / L.

[0054] The test results are shown in Table 2 below: Table 2 Test results

[0055] In Table 2, compared with Examples 6 to 8, the anchor rods prepared in Examples 9 to 14 did not have rust on the surface after the acetic acid salt spray test, and the corrosion resistance rate was significantly reduced after the anchor rods were subjected to a weekly immersion test, indicating that when carboxymethyl glucan and iminodisuccinic acid were added to the passivation solution, carboxymethyl glucan and iminodisuccinic acid had a synergistic effect, which could further improve the corrosion resistance of the anchor rod. Compared with Examples 10 to 12, the anchor rods prepared in Examples 13 to 14 did not have rust on the surface after the acetic acid salt spray test, and the corrosion resistance rate was significantly reduced after the anchor rods were subjected to a weekly immersion test, indicating that when the weight ratio of carboxymethyl glucan to iminodisuccinic acid was 1 to 1.5:1, the corrosion resistance of the anchor rod could be further improved. In addition, compared with Example 14, after the anchor rods prepared in Examples 15 to 18 were subjected to an acetic acid salt spray test, no rust appeared on the surface, and after the anchor rods were subjected to a circumferential immersion test, the corrosion resistance rate decreased, indicating that the surface modification of nano silicon nitride using ternary hydroxychloroacetic resin can further improve the corrosion resistance of the anchor rod. Compared with Examples 15 to 16, after the anchor rods prepared in Examples 17 to 18 were subjected to an acetic acid salt spray test, no rust appeared on the surface, and after the anchor rods were subjected to a circumferential immersion test, the corrosion resistance rate decreased, indicating that when the weight ratio of nano silicon nitride to ternary hydroxychloroacetic resin is 9 to 19:1, the corrosion resistance of the anchor rod can be further improved.

[0056] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A corrosion-resistant anchor rod, obtained by hot-dip galvanizing and passivation treatment of the anchor rod body, characterized in that: The anchor body is composed of the following components in weight percentage: Mn 0.55%~0.75%, Mo 0.035%~0.055%, C 0.15%~0.25%, Dy 0.015%~0.035%, V 0.05%~0.25%, Gd 0.025%~0.045%, W 0.01%~0.025%, and the rest are iron and unavoidable impurities.

2. A corrosion-resistant anchor rod according to claim 1, characterized in that: The weight ratio of Dy and W to Mo is 0.8-1:

1.

3. The corrosion-resistant anchor rod according to claim 1, characterized in that: The weight ratio of Dy to W is 1:

1.

4. A production process for a corrosion-resistant anchor according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing the components in the weight percentage, smelting, and casting to obtain a casting billet; S2, heat-treating the ingot, rolling, drawing, and threading the ingot to obtain an anchor body; S3, the anchor body is pickled, washed with water, hot-dip galvanized, passivated and cooled to obtain a corrosion-resistant anchor.

5. The production process of a corrosion-resistant anchor rod according to claim 4, characterized in that: In step S3, during the passivation, a passivation solution is used, and the passivation solution includes the following components in parts by weight: 25-35 parts of chromium nitrate, 3-18 parts of carboxymethyl dextran, 10-15 parts of sodium molybdate, 4-11 parts of iminodisuccinic acid, 6-10 parts of potassium sodium tartrate, 8-22 parts of nano silicon nitride, and 100 parts of water.

6. The production process of a corrosion-resistant anchor rod according to claim 5, characterized in that: The weight ratio of the carboxymethyl glucan to the iminodisuccinic acid is 1-1.5:

1.

7. The production process of a corrosion-resistant anchor rod according to claim 5, characterized in that: The nano silicon nitride is modified nano silicon nitride, and the raw materials of the modified nano silicon nitride include nano silicon nitride and ternary hydroxychloroacetic acid resin.

8. The production process of a corrosion-resistant anchor rod according to claim 7, characterized in that: The preparation method of the modified nano silicon nitride comprises the following steps: dissolving the ternary hydroxychloroacetate resin in ethyl acetate to obtain a ternary hydroxychloroacetate resin solution, adding the nano silicon nitride to the ternary hydroxychloroacetate resin solution, dispersing evenly, and concentrating to obtain the modified nano silicon nitride.

9. The production process of a corrosion-resistant anchor rod according to claim 7, characterized in that: The weight ratio of the nano silicon nitride to the ternary hydroxychloroacetic acid resin is 9-19:

1.

10. The production process of a corrosion-resistant anchor rod according to claim 4, characterized in that: In step S2, during the heat treatment, the temperature is 1000-1200° C. and the insulation time is 30-60 min.

Citation Information

Patent Citations

  • Method for preparing high-corrosion-resistance aluminum alloy trivalent chromium composite conversion coating

    CN105420714A

  • Production method for high-toughness MG600 hot-rolling anchor rebar

    CN109234619A

  • Passivation treatment process for soft magnetic metal powder for inductor forming

    CN113426994A

  • Steel sheet and production method for same

    CN113574197A

  • Corrosion-resistant pipe seam type anchor rod and preparation method thereof

    CN116574996A